2015
DOI: 10.1021/jacs.5b03827
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Behavior and Enhanced Wet-Cohesion of Synthetic Copolyampholytes Inspired by a Mussel Foot Protein

Abstract: Numerous attempts have been made to translate mussel adhesion to diverse synthetic platforms. However, the translation remains largely limited to the Dopa (3,4-dihydroxyphenylalanine) or catechol functionality, which continues to raise concerns about Dopa's inherent susceptibility to oxidation. Mussels have evolved adaptations to stabilize Dopa against oxidation. For example, in mussel foot protein 3 slow (mfp-3s, one of two electrophoretically distinct interfacial adhesive proteins in mussel plaques), the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
144
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(148 citation statements)
references
References 22 publications
2
144
0
1
Order By: Relevance
“…[8] The interaction between Fe 3+ and mfp-1 using surface sensitive and solution phase techniques showed that the mfp-1 homologs bind Fe 3+ differently: mfp-1 ( Mc ) Dopa groups interact with Fe 3+ to form intramolecular complexes, whereas mfp-1 ( Me ) Dopa groups form intermolecular complexes. [8] Similarly, the adhesive and cohesive contributions of residues other than Dopa in other mfps are the topic of recent studies [89] and will be discussed later.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The interaction between Fe 3+ and mfp-1 using surface sensitive and solution phase techniques showed that the mfp-1 homologs bind Fe 3+ differently: mfp-1 ( Mc ) Dopa groups interact with Fe 3+ to form intramolecular complexes, whereas mfp-1 ( Me ) Dopa groups form intermolecular complexes. [8] Similarly, the adhesive and cohesive contributions of residues other than Dopa in other mfps are the topic of recent studies [89] and will be discussed later.…”
Section: Introductionmentioning
confidence: 99%
“…The literature contains a variety of synthetic adaptations, with emphasis on the reduced complexity and improved tractability of the structure and adhesive mechanism. Examples include a random copolymer in which positively and negatively charged acrylates are incorporated, a hydrophobic aryl moiety, a catechol, or a neutral hydrophobic group; but also a small molecule that incorporates the aforementioned characters, and, finally, synthetic peptide mimics of the P. californica , sandcastle worm, adhesives …”
Section: Mussel Inspired Materialsmentioning
confidence: 99%
“…Additionally, the balanced charge (equal number of cationic and anionic charges) in individual repeating unit acts as a buffer, providing stability over a wide range of pH in aqueous biological solutions. The ionic charges in a zwitterionic polymer also serves to increase oxidative stability via electrophilic shielding in a coacervate environment . Finally, the methacrylate moiety of the zwitterionic monomer allows for convenient radical polymerization in the preparation of desirable polymeric adhesives.…”
Section: Introductionmentioning
confidence: 99%